Word Valence and Syntactic Relationship - Ravshankhodja, Rasulov (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the word, the valence of the word and the syntactic connection between them. In it, the word embeds as a bearer of all its just properties, qualities and relationships. A substantial approach to the word summarizes the results of the study of lexical-semantic and grammatical tiers; these tiers appear in dialectical unity. In speech, the semantics of a single word interacts with the semantic structure of the whole utterance.At present, the basic laws governing the combination of one unit of language with another are united by the concept of valence. The valence of a word as a substantial-semantic fact is connected with the meaning of the word and the realization of its meaning in the construction of the sentence.The semantic relation between words directly reveals a syntactic relation, which is fixed in the formation of syntactic construction, since semantic relations exist on the basis of syntactic ones.